Reflections on the integral human being and the conception of health - Mariana Marques Arantes; Aurino Lima Ferreira (Universidade de Pernambuco, 2019)
Present a multidimensional and integral view of the human being, from contemporary philosophical contributions to contribute with reflections on the conception of health today. Reflection article with hermeneutic methodology. Aprocess of cultivation is required for self-knowledge that leads to an understanding of what constitutes human beings, the awareness of the unity that enables beings to connect with one another and the environment in which they live.The complexification of the look on what it means to be a human being and what it means to be healthy should recognize the multidimensionality and indivisibility of culture to think about health promotion processes for the integral human being.